Practical software process improvement - Fantina, Robert (Artech House, 2005)
Based on CMM®/CMMI®, this unique new resource offers you practical "how to" guidance on software process improvement. The book provides you with clear implementation steps that are designed to have a highly positive impact on even your most challenging projects. You get valuable, time-saving templates that can be quickly tailored for your purposes and used immediately. The book reveals the most common problem areas that effect projects and processes, and offers specific advice on how to overcome these pitfalls. You learn how to assess the strengths and weaknesses of your organization and your specific projects, and discover the most effective ways to address the critical areas that need attention. Publisher abstract.
Keywords: Computer software -- Development -- Management.; Project management.; Gestion de projet.; COMPUTERS -- Software Development & Engineering -- Project Management.; Computer software -- Development -- Management